2019
DOI: 10.1097/md.0000000000015092
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of tenofovir or telbivudine in preventing HBV vertical transmission for pregnancy

Abstract: To evaluate the efficacy and safety of telbivudine (LdT) and tenofovir (TDF) for preventing hepatitis B virus (HBV) vertical transmission for HBV-positive pregnant women. Pregnant women (n = 145) from January 2013 to June 2017 were enrolled when they met inclusion criteria, which included HBV DNA ≥1.0 × 10 7 copies/mL and increased alanine aminotransferase (ALT) levels. Groups A (n = 58) and B (n = 51) were treated with LdT and TDF, respectively. Group C (n = 36) received no a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 25 publications
0
27
0
1
Order By: Relevance
“…22 In a study by Zeng et al, it was reported that pregnant women treated with TDF or LDT did not develop drugrelated complications and that vertical transmission was effectively and safely prevented. 23 Nachega et al reported that, in a meta-analysis covering HIV or HBV-infected pregnant women, antiretroviral treatment including TDF was safe for mother and baby. 7 When the literature is reviewed, case reports show that the use of TDF in pregnant women is safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…22 In a study by Zeng et al, it was reported that pregnant women treated with TDF or LDT did not develop drugrelated complications and that vertical transmission was effectively and safely prevented. 23 Nachega et al reported that, in a meta-analysis covering HIV or HBV-infected pregnant women, antiretroviral treatment including TDF was safe for mother and baby. 7 When the literature is reviewed, case reports show that the use of TDF in pregnant women is safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…Effective agents in the treatment of chronic HBV infection are Pegylated Interferon, lamivudine, entecavir, adefovir, telbivudine and tenofovir. However, telbivudine, lamivudine and tenofovir are usually preferred in pregnancy because of the more number of studies related to their safe use in pregnancy (7,10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Among the selected studies, 3 RCTs [7-9] and 12 non-RCTs [10,[16][17][18][19][20][21][22][23][24][25][26] compared treatment started in the third trimester versus control, 7 non-RCTs compared the timing of second trimester versus control [27][28][29][30][31][32][33], 3 non-RCTs compared first trimester versus control [14,34,35], 4 non-RCTs compared second and third trimester versus control respectively [11,[36][37][38], 3 non-RCTs compared first, second trimester versus control respectively [39][40][41]; 2 non-RCTs compared first, third trimester versus control respectively [12,42], 1 non-RCTs compared first, second trimester, third trimester versus control respectively [13]. No randomized controlled trials were conducted for the treatment that was applied during first or second trimester except for several non-RCTs.…”
Section: Characterization and Quality Of Studiesmentioning
confidence: 99%
“…Forest plot of pair-wised meta-analysis of MTCT at 6-12 months after delivery for non-RCTs. a Antiviral therapy ~ 28 week versus control, b [28][29][30][31][32] week versus control at 6-12 months after delivery. c ~ 28 week versus 28-32 week…”
Section: Figmentioning
confidence: 99%